The role of logistics in food waste reduction in wholesalers and small retailers of fruits and vegetables: A multiple case study - Patricia Guarnieri; Raiane C. C. de Aguiar; Karim Marini Thomé; Eluiza Alberto de Morais Watanabe (Logistics, 2021)
Background: There is a lack of studies on the waste of fruits and vegetables covering both distributors and the retail sector. Our study advances from previous ones by proposing the analysis of local retailers of different sizes and wholesalers. Our objective was to analyze the logistical practices to reduce the waste of fruits and vegetables in wholesalers and small retailers in Federal District, Brazil. Methods: A multiple case study was conducted with 19 retailers and eight wholesalers. We administered semi-structured interviews and performed documental analysis and direct observation. Results: The findings demonstrated the leading logistical practices of handling, conservation, management and control, and consumer awareness about food waste. The type of retailer was limited to grocery stores and fruit shops, and the type of food covered only fruits and vegetables. Furthermore, we considered the food waste generated in the logistics processes and not that after consumption. Conclusions: More than a third of the food produced worldwide is lost or wasted. A considerable part of the food waste is associated with the lack of an adequate structure of the logistical processes. The results may contribute to the adoption of practices related to reducing food waste by retailers and wholesalers.
Keywords: 650; food waste; logistics; retail; supply chain management; wholesale